UTILIZATION OF MULTITEMPORAL LANDSAT DATA FOR COASTLINE CHANGE ANALYSIS USING CANNY EDGE DETECTOR - Luhur Moekti Prayogo; Zainul Hidayah (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2021)
ABSTRACTThe development of remote sensing technology has experienced significant progress. This progress is marked by the availability of images of various resolutions with complete channels, open-source, and their development in various image classification techniques such as edge detection techniques. This study aims to examine changes in the coastline in Banmaleng Village, Gili Raja Island, Sumenep Regency using the Canny edge detection algorithm on multitemporal Landsat 7 and 8 imagery in 2005 - 2020. The edging process includes (a) minimize noise by applying a Gaussian filter, (b) determine the image intensity gradient, (c) apply non-maximum emphasis to eliminate spurious responses to objects, (d) define multiple thresholds for determining potential image edges, (e) Track edge hysteresis by pressing all other weak edges that are not connected to firm edges. Canny edge detection produces sharp edges to analyze coastline changes quite well. Every five years, the coastline of Banmaleng Village experienced shifting from 0,4 to 2,3 meters in several areas.Keywords: Edge Detection, Landsat, Coastline, Canny Algorithm, Gili Raja